Integrative analysis of m7G methylation-associated genes prognostic signature with immunotherapy and identification of LARP1 as a key oncogene in head and neck squamous cell carcinoma - Xu, Juan; You, Zihao; Zhu, Zhongping; Liu, Min; Zhang, Zheng; Xu, Panpan; Dong, Juanjuan; Huang, Yuting; Wang, Chao; Qin, Haotian (Frontiers in Immunology, 2025)
BackgroundN7-methylguanosine (m7G) methylation is an RNA modification associated with cancer progression, but its specific role in head and neck squamous cell carcinoma (HNSCC) remains unclear.MethodsThis study analyzed the differential expression of m7G-related genes (m7GRGs) in HNSCC using the TCGA-HNSCC dataset, identifying key pathways associated with the cell cycle, DNA replication, and focal adhesion. A LASSO-Cox regression model was constructed based on four m7GRGs (EIF3D, EIF1, LARP1, and METTL1) and validated with GEO datasets and clinical samples. Further validation of gene upregulation in HNSCC tissues was conducted using RT-qPCR and immunohistochemistry, while the role of LARP1 in HNSCC cells was assessed via knockout experiments.ResultsThe constructed model demonstrated strong predictive performance, with the risk score significantly correlating with prognosis, immune infiltration, and drug sensitivity. An external dataset and clinical specimens further confirmed the model’s predictive accuracy for immunotherapy response. Additionally, two regulatory axes—LINC00707/hsa-miR-30b-5p/LARP1 and SNHG16/hsa-miR-30b-5p/LARP1—were identified. LARP1 knockout experiments revealed that suppressing LARP1 markedly inhibited HNSCC cell proliferation, migration, and invasion.ConclusionThe m7GRG-based prognostic model developed in this study holds strong clinical potential for predicting prognosis and therapeutic responses in HNSCC. The identification of LARP1 and its related regulatory pathways offers new avenues for targeted therapy in HNSCC.